2D catalysts for electrochemical oxygen reduction reactions - Brata, Jason Jovi (Nanyang Technological University, 2022)
Metallic dual-atom catalysts have been demonstrated to be highly promising catalysts for oxygen reduction reaction (ORR), replacing traditional Pt-based catalysts. Theoretical simulations as well as experiments have been done to characterize the performance of these catalysts. However, it is still in debate whether current theoretical simulations can accurately represent the catalysts in real life. Herein, we design 3 different metallic dual-atom catalysts (namely Fe2N6, Co2N6, and FeCoN6 in graphene) and analyze the overall reaction of oxygen reduction on these catalysts using density functional theory calculations. After considering extra factors, which includes an unconventional 2OH* pathway and charge effect on the catalysts, Fe2N6 and FeCoN6 display superior performance with working potential of 0.908V and 0.813V, respectively. These values are higher than the working potential of traditional Pt-based catalysts (0.78V), which shows that they are suitable to be alternatives for ORR catalysts. The scope of this project can also be extended to other metallic dual-atom catalysts (Cu, Mn, Zn, Ni, etc.), and possibly for catalysts used for different processes, such as for H2 evolution, N2 reduction, or CO2 reduction.